On the correction of altered ocular hemodynamics in acute ischemic optic neuropathy (Ukrainian Journal of Ophthalmology, 2026)
Background: Vascular optic nerve disorders are the second most common incapacitating ocular condition (19%) in Ukraine. Inadequate efficacy of available therapies calls for the search of medications that would improve ocular hemodynamics in this disease.Purpose: To investigate the influence of sulodexide on ocular hemodynamics in acute ischemic optic neuropathy.Materials and Methods: Twenty-seven acute ischemic optic neuropathy patients (27 eyes) underwent clinical studies at baseline and after 15-day adjuvant treatment with Vessel due F (2.0 mL intramuscular injection daily). The control group included 29 acute ischemic optic neuropathy patients (29 eyes) treated by therapy without adjuvant Vessel due F. All patients underwent Doppler ultrasonography of the ophthalmic artery with LOGIQ 3 Expert (GE, USA) apparatus.Results: After treatment, Doppler ultrasonography indices improved only in patients of the study group, with 28% increased mean peak blood flow velocity and 31% increased mean minimum blood flow velocity in the ophthalmic artery, and 15% decreased vascular resistance index. No significant changes in these parameters were observed in the controls.Conclusion: The use of adjuvant Vessel due F corrected the altered regional ocular hemodynamics and resulted in improved treatment outcomes in acute ischemic optic neuropathy patients.
Keywords: acute ischemic optic neuropathy; Doppler ultrasonography; ophthalmic artery; Vessel due F